Peripheral Vascular Anomalies – Essentials in Periinterventional Imaging - Sadick, Maliha; Overhoff, Daniel; Baessler, Bettina; von Spangenberg, Naema; Krebs, Lena; Wohlgemuth, Walter A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Peripheral vascular anomalies represent a rare disease with an underlying congenital mesenchymal and angiogenetic disorder. Vascular anomalies are subdivided into vascular tumors and vascular malformations. Both entities include characteristic features and flow dynamics. Symptoms can occur in infancy and adulthood. Vascular anomalies may be accompanied by characteristic clinical findings which facilitate disease classification. The role of periinterventional imaging is to confirm the clinically suspected diagnosis, taking into account the extent and location of the vascular anomaly for the purpose of treatment planning.Method In accordance with the International Society for the Study of Vascular Anomalies (ISSVA), vascular anomalies are mainly categorized as slow-flow and fast-flow lesions. Based on the diagnosis and flow dynamics of the vascular anomaly, the recommended periinterventional imaging is described, ranging from ultrasonography and plain radiography to dedicated ultrafast CT and MRI protocols, percutaneous phlebography and transcatheter angiography. Each vascular anomaly requires dedicated imaging. Differentiation between slow-flow and fast-flow vascular anomalies facilitates selection of the appropriate imaging modality or a combination of diagnostic tools.Results Slow-flow congenital vascular anomalies mainly include venous and lymphatic or combined malformations. Ultrasound and MRI and especially MR-venography are essential for periinterventional imaging. Arteriovenous malformations are fast-flow vascular anomalies. They should be imaged with dedicated MR protocols, especially when extensive. CT with 4D perfusion imaging as well as time-resolved 3D MR-A allow multiplanar perfusion-based assessment of the multiple arterial inflow and venous drainage vessels of arterio-venous malformations. These imaging tools should be subject to intervention planning, as they can reduce procedure time significantly. Fast-flow vascular tumors like hemangiomas should be worked up with ultrasound, including color-coded duplex sonography, MRI and transcatheter angiography in case of a therapeutic approach. In combined malformation syndromes, radiological imaging has to be adapted according to the dominant underlying vessels and their flow dynamics.Conclusion Guide to evaluation of flow dynamics in peripheral vascular anomalies, involving vascular malformations and vascular tumors with the intention to facilitate selection of periinterventional imaging modalities and diagnostic and therapeutic approach to vascular anomalies.Key Points: Citation Format
Keywords: blood vessels; angiography; diagnostic radiology; embolization; interventional procedures; CT angiography